Disaster evacuation challenges in high-density urban neighborhood Kampung Code, Yogyakarta (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The article discusses the challenges of disaster evacuation in the high-density urban neighborhood of Kampung Code in Yogyakarta, Indonesia. The rapid urbanization along riverbanks in the area has led to increased vulnerability to flooding and other environmental hazards. The study aims to identify the characteristics and challenges of circulation routes for supporting disaster evacuation in riverbank settlements like the Kampung Code. The research uses a mixed-methods approach, including surveys, interviews, and observations, to gather data using a town-watching approach. The article emphasizes the importance of understanding the specific characteristics of space in these areas to enhance community resilience and disaster recovery. The study occurred in Kampung Jogoyudan, one of the most populated areas along the Code River, and serves as a model for understanding and addressing evacuation challenges in other high-density urban environments.
Keywords: Disaster; Evacuation; High-density Kampung